Academic production and technological emergence in finance: Bibliometric study on FinTechs - Itamir Caciatori Junior; Ana Paula Mussi Szabo Cherobim (Innovation & Management Review, 2020)
Purpose - This paper aims to study the FinTech enterprises and the management theories related to this subject in a scientific way. Design/methodology/approach - This study is a bibliometric study on FinTech enterprises. Its origin is a survey of 1,749 papers in 6 traditional peer-reviewed academic databases (e.g. Science Direct and Scopus) and in the "gray" literature, published by other agents and not subject to double-blind peer review. In this analysis we use three approaches: academic paper or not; journal main interest, and main purpose of the paper. Findings - The first approach shows 45% of papers without blind review. The second approach shows no concentration on any journal. It represents no concentration on any kind of specific journal. And the third approach shows four kinds of contents in all researched papers: FinTech categorizations; FinTech related to theory of disruptive innovation; FinTech and theories of administration or economy; and finally, FinTech and regulatory and legislative aspects. Originality/value - The findings identified the emergence of new research strands, precedence of studies of "gray" literature to explain the phenomenon, distribution of studies in different fields of knowledge (e.g. information technology, business and law) and lack of consensus in theories to explain the matter.
Keywords: 650; Bibliometry; Financial technologies; FinTechs; Grey literature; Innovation